How low can you go: Achieving postoperative outpatient pain control without opioids. Issue 1 (July 2019) - Sim, Vasiliy; Hawkins, Samuel; Gave, Asaf A.; Bulanov, Alex; Elabbasy, Fady; Khoury, Leen; Panzo, Melissa; Sim, Elizabeth; Cohn, Stephen
Abstract : BACKGROUND: Postoperative outpatient narcotic overprescription plays a significant role in the opioid epidemic. Outpatient opioid prescription ranges from 150 to 350 oral morphine equivalent (OME) for a laparoscopic cholecystectomy or appendectomy, with 75 OME (10 pills of 5 mg of oxycodone) being the lowest recommendation (National Institute on Drug Abuse, 2018). We hypothesized that the addition of nonopioid medications to the outpatient pain control regimen would decrease the need for narcotics. METHODS: In this prospective, observational pilot study, we prescribed a 3-day regimen of ibuprofen and acetaminophen to patients after uncomplicated laparoscopic cholecystectomies and appendectomies. An additional opioid prescription for 5 pills of 5 mg of oxycodone (37.5 OME) was written for breakthrough pain. During their postoperative visit, we evaluated patients' adherence to the pain control regime, their postdischarge opioid use, and the adequacy of their pain control. RESULTS: Sixty-five patients were included in the study (52% male). The majority (80%) of surgeries were performed urgently or emergently. The visual analog scale pain score at home was significantly better than upon discharge (3.7 vs. 5.5, p = 0.001). The average number of oxycodone pills taken postdischarge was 1.8 pills. Half (51%) of the patients did not take any opioids. All but four patients reported that their pain was adequately controlled. No patient required additional opioid prescriptions or visited the emergency department. CONCLUSION: This study demonstrated that opioids can be eliminated in at least half of the patients and that five pills of 5 mg of oxycodone (37.5 OME) is sufficient for outpatient pain control when a 3-day course of ibuprofen and acetaminophen is prescribed. LEVEL OF EVIDENCE: Therapeutic study, level V.